Parameters associated with survival in patients undergoing surgical treatment due to rectal cancer - Gursul, Serdar; İflazoğlu, Nidal; Karabulut, Koray; Saraç, Mehmet (My University, 2019)
Aim: Colorectal cancer is the third most common type of cancer.Approximately 1/3 of colorectal cancers are rectum cancers. Thepercentage of local disease stage is 39%, and the 10-year survival rate in such patients is approximately 90%. The aim of our studywas to evaluate the relationship between the clinicopathological characteristics and survival of patients with rectal cancer.Material and Methods: Patients who had undergone surgical treatment for rectal cancer in our clinic between January 2008 andDecember 2013 were evaluated retrospectively. The effects of clinicopathological parameters of these patients on survival wereinvestigated. The preoperative and postoperative variables were evaluated together with survival data.Results: Of the 70 patients, 30 (43%) were females and 40 (57%) were males. The median age was 61 years (min-max = 29-87 years).Eight of the patients (6%) were operated under emergency conditions due to acute abdomen or ileus. 13 (19%) of the patients hadundergone laparoscopic surgery and 57 (81%) had undergone open surgical resection. 15 patients (21%) had undergone anteriorresection (AR), 51 (73%) had lower anterior resection (LAR) and 4 (6%) had abdomino-perineal resection (APR). According to pTNMstaging, 6 patients (8%) were at stage-0, 7 (10%) were at stage-I, 22 (32%) were at stage-II, 26 (37%) were at stage-III, and 9 (13%)were at stage IV.Conclusion: We found that the ASA (American society of Anesthesiologists) score height, final stage of the tumor and vascular(venous) invasion associated with overall survival
Keywords: Genel ve Dahili Tıp; Onkoloji; Cerrahi